Digital awareness from the ground up – safe development of algorithmic thinking through unplugged activities - Meggyesi István; Kuchinka Katalin; Kucsinka Katalin; Кучінка Каталін (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In the 21st century, the rapid expansion of digital technologies has made the development of digital awareness and algorithmic thinking a fundamental objective of modern education. Algorithmic thinking is widely recognized as a core cognitive competence that supports logical reasoning, abstraction, decomposition, and problem-solving skills, which together form the basis of digital literacy and computational understanding across disciplines [1]. Preparing students to navigate the digital world responsibly therefore requires not only technical knowledge but also reflective, structured ways of thinking. Recent educational research emphasizes the effectiveness of unplugged pedagogical methods— learning activities that introduce computational concepts without the use of digital devices— particularly in early and primary education [2]. Through logical and physical games such as sequencing tasks, role-based algorithms, movement-based coding, and problem-solving puzzles, learners can internalize fundamental algorithmic principles in an age-appropriate and engaging manner. These activities transform abstract computational ideas into tangible experiences, enabling students to construct mental models of algorithms before encountering formal programming languages.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: digital awareness; algorithmic thinking